Vocational Life Skills in Religious Education: Lessons Learned from Three Islamic Boarding Schools in Java - Noorhayati, Siti Mahmudah; Hakim, Abdurrahman; Fata, Ahmad Khoirul (JURNAL AT-TURAS, 2023)
This research is based on the idea of the need for the development of self-reliant enterprises in educational institutions (Islamic boarding schools) to create institutional and graduate independence. Based on this, the Ministry of Religious Affairs of the Republic of Indonesia (MORA) created a program in 2021 related to the development of vocational life skills and self-reliance for Islamic boarding schools. This study includes field research where data is obtained through participatory observation, field documentation, and in-depth interviews using a qualitative approach and qualitative descriptive analysis method. This research presents several new findings: First, the concept of vocational life skills is realized through a Business Incubation program based on household products. Second, the Legal Entity of Islamic Boarding School Enterprises (BUMPES) accommodates various units for the development of small businesses that optimally assist in production management and marketing of creative products from Islamic boarding schools to the general public. Third, training or workshops are provided to students (santri) as workers or human resources involved in this small business process, involving the required experts. Fourth, there are still shortcomings in empowering student workers in this business development because human resource management is needed in production management. This program has provided a beneficial contribution to the progress of Islamic boarding school education, particularly in enhancing the quality of vocational life skills education and understanding of the business world or micro, small, and medium enterprises (MSMEs).